Government Support, Active Participation of Families and Optimistic Vision of the Future During the COVID-19 Emergency: Results of a Longitudinal Research Study - Moscatelli, Matteo; Carrà, Elisabetta; Ferrari, Chiara (Italian Sociological Review, 2022)
The emergency caused by the COVID-19 pandemic has caused the Italian government to run the risk of strengthening a welfare regime which is still too widespread and that delegates to families the answers to social needs, taking for granted their willingness to act. Through data from the first and second waves of a longitudinal research project entitled ‘The family at the time of COVID-19’ (W1, N=2,985: W2, N=2,191), it has been possible to highlight a certain disagreement on the capacity of the government to support families effectively during the most critical period of the pandemic in Italy (March–April 2020) and when the pandemic was less rampant (July 2020), despite entrusting these families with several crucial tasks and functions. Data from both waves also show that feeling supported by the government as a family is closely related to an optimistic vision of the future and the belief in the possibility that families can contribute to social change. These results suggest that participants are geared to a subsidiary welfare regime, in which families, with support from the government, play a crucial role as agents of social change.